HEALTH EDUCATION ON FAMILY MEDICINE PRINCIPLES FOR PROLANIS DIABETES MELLITUS GROUPS AT A PRIMARY CARE CENTER IN JAMBI CITY - Darmawan, Armaidi; aurora, Wahyu Indah Dewi; Kusdiyah, Erny; Syauqy, Ahmad; Sulistiawan, Andika; Nuriyah, Nuriyah (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2024)
Diabetes Mellitus (DM) is a growing public health concern worldwide, including in Indonesia. The Indonesian Chronic Disease Management Program (PROLANIS) aims to empower individuals and families affected by DM through community-based health education. This study employed an educational intervention delivered through a counseling session on the importance of family medicine principles and dietary management for DM patients. A pre-test was administered to assess the participants' baseline knowledge, followed by the educational session, and concluded with a post-test. A total of 37 participants were involved in this activity, the majority of whom were middle-aged women with a senior high school level of education. Pre-test results indicated that 57% of participants had a low level of understanding. However, the post-test revealed a significant improvement, with 76% of participants achieving a score in the 6-10 range. Nevertheless, some participants still required further guidance. Despite the observed increase in knowledge, the application of family medicine principles within the PROLANIS program in the working area of the Rawasari Community Health Center remains suboptimal. The active engagement of participants during the question-and-answer session highlighted the need for additional support in implementing these principles. The educational program successfully enhanced participants' understanding of diabetes management. However, continuous monitoring and periodic evaluation by the Community Health Center and community health workers (cadres) are necessary to improve the application of family medicine principles within the PROLANIS program in its designated area. Keywords: Diabetes Mellitus, PROLANIS, Family Medicine